Assessment of Dental Student Satisfaction after Internships in Collaborative Dental Practices in Saxony-A Retrospective Questionnaire Analysis - Annette Wolf; Mihaela Pricop-Jeckstad; Ute Botzenhart; Tomasz Gredes (MDPI AG, 2024)
The goal for dental students of a university-based program should be to learn about practice procedures in a dental office as part of their studies in order to gain insight into day-to-day activities, such as organizational management, patient communication, and problem-solving strategies. All dental students from the Faculty of Medicine at the University of Dresden in Germany, who completed a one-week internship in an external dental office in the last year before taking the final exam, were invited to participate in the survey (total n = 182 in years 2017-2019 and 2022). After completing the internship, the students were asked to anonymously rate the distinctive competencies they had acquired during their dental studies in terms of clinical and social communication skills. The results of the survey showed a good practicability of the acquired dental knowledge and a general satisfaction of students during their internships. No significant influence of the COVID-19 outbreak and the resulting special regulations in dental practices during the pandemic on student satisfaction was found. Students were more satisfied with their completed internships in smaller cities. Therefore, a stronger inclusion of practices outside the big cities should be considered in the current implementation of the new Dental Licensure Act in Germany.